2013
DOI: 10.1093/joclec/nht017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Antitrust Leniency Programs

Abstract: This paper identifies and then quantifies econometrically the impact of leniency programs on the perception of the effectiveness of antitrust policies in the business community using panel data for as much as 59 countries and 14-year span. We use the dynamics of the gradual diffusion of leniency programs across countries and over time to evaluate the impact of the program, taking care of the bias caused by self-selection into the program. We find that leniency programs increase the perception of effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…The CP literature has demonstrated that leniency programs were effective in general and their introduction represented a critical juncture that allowed NCAs to better enforce the law (Dasgupta & Žaldokas, 2019;Dong, Massa & Žaldokas, 2019;Ordóñez-De-Haro, Borrell & Jiménez, 2018). More important, Borrell, Jiménez, & García (2014) show that the adoption of leniency programs significantly increases the 'perception' of CP effectiveness (not only with reference to collusion), thus acting as "a weapon of mass dissuasion in the hands of antitrust enforcers" (Borrell et al, 2014: 107). This evidence definitely supports our choice of the staggered passage of those programs as a proxy for a general positive change in the perceived status of CP enforcement.…”
Section: Variables and Sourcesmentioning
confidence: 99%
“…The CP literature has demonstrated that leniency programs were effective in general and their introduction represented a critical juncture that allowed NCAs to better enforce the law (Dasgupta & Žaldokas, 2019;Dong, Massa & Žaldokas, 2019;Ordóñez-De-Haro, Borrell & Jiménez, 2018). More important, Borrell, Jiménez, & García (2014) show that the adoption of leniency programs significantly increases the 'perception' of CP effectiveness (not only with reference to collusion), thus acting as "a weapon of mass dissuasion in the hands of antitrust enforcers" (Borrell et al, 2014: 107). This evidence definitely supports our choice of the staggered passage of those programs as a proxy for a general positive change in the perceived status of CP enforcement.…”
Section: Variables and Sourcesmentioning
confidence: 99%
“…It may lead to the decrease of their variety and to the selective application of only those most cost-efficient. Leniency programmes have recently become the most preferable method [21,[28][29][30]. Their beginnings extend to the 1970s, when the first leniency programme was implemented in the USA.…”
Section: Classification Of Anti-competitive Agreement Detection Methodsmentioning
confidence: 99%
“…There is an empirical literature that evaluates, through survey-based indicators, the perception of the effectiveness of competition policy in a country. The main references are those of Nicholson (2008), Borrell and Jiménez (2008), Voigt (2009), Ma (2010Ma ( , 2012Ma ( , 2013, Gutmann andVoigt (2014), andBorrell et al (2014). All of them use two main sources: those elaborated by the World Economic Forum and those collected annually by the International Institute for Management Development (IMD).…”
Section: Literature Reviewmentioning
confidence: 99%